The Effect of Electronic Service Quality and Promotion on the PLN Mobile Application on PLN ULP Sungguminasa Customer Satisfaction in Gowa Regency in the Era of the Covid-19 Pandemic - Nur Inaya Magfirah; Amiruddin Tawe; Muhammad Ilham Wardhana Haeruddin; Zainal Ruma; Muhammad Ichwan Musa (International Humanity Advance, Business & Sciences, 2023)
The purpose of this study was to determine the effect of the quality of e-services and promotions on the PLN Mobile application on customer satisfaction at PLN ULP Sungguminasa in Gowa Regency using the PLN Mobile application. The sampling technique uses a non-probability sampling model with a purposive sampling method. The method used in this research is quantitative. Then for the analysis technique using multiple linear regression analysis. Based on the results of hypothesis testing as a whole, it shows that the e-service quality and promotion variables simultaneously have a positive and significant effect on customer satisfaction as users of the PLN Mobile application and the results of the partial hypothesis test show that the e-service quality variable has a positive and significant effect.